Comparison of Intraarticular Ketorolac Versus Triamcinolone Acetone Injection in Patients of Knee Osteoarthritis - Soban Sarwar Gondal, Abeera Zareen, Muhammad Haroon Anwar, Jawad Zaheer, Muhammad Salim (Journal of Rawalpindi Medical College, 2021)
Objective: To compare the analgesic and functional outcomes of intra-articular ketorolac with corticosteroids in patients of knee OA. Methods: In this randomized comparative study, we included patients of knee OA who were planned for intra-articular injections from January-2020 to December-2020 in the Department of Anesthesia and Pain Medicine at Rawalpindi Medical University. Patients were allocated to two groups using block randomization, each block contained 30 patients and received injection of either triamcinolone (Group T) or ketorolac (Group K). VAS score and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score were noted at 1 week, 1 month and at 3 months of injection. Results: Mean baseline WOMAC score was 46.60±5.64 in group K and 47.0±5.27 in group T (p-value 0.74). Mean WOMAC score was reduced significantly at 1st week and 1 months and 3 months follow-up in both groups, with insignificant statistical difference in group K and T (p-value 0.39, 0.18 & 0.15 respectively). Baseline VAS score was 7.02±1.34 in group K versus 7.27±1.03 in group T (p-value 0.36). VAS score was also reduced at 1 week, 1 month and 3 months follow-up, however the mean VAS at intervals was not statistically different between group K and T with p-value of 0.13, 0.08 and 0.49 respectively. Treatment was successful in 22 (55%) patients in group K versus 24 (60%) patients in group T (p-value 0.65). Conclusion: Intraarticular ketorolac has similar functional and analgesic outcomes as that of triamcinolone.